2020
DOI: 10.1084/jem.20192080
|View full text |Cite
|
Sign up to set email alerts
|

Layilin augments integrin activation to promote antitumor immunity

Abstract: Tumor-infiltrating CD8+ T cells mediate antitumor immune responses. However, the mechanisms by which T cells remain poised to kill cancer cells despite expressing high levels of inhibitory receptors are unknown. Here, we report that layilin, a C-type lectin domain–containing membrane glycoprotein, is selectively expressed on highly activated, clonally expanded, but phenotypically exhausted CD8+ T cells in human melanoma. Lineage-specific deletion of layilin on murine CD8+ T cells reduced their accumulation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 48 publications
0
44
2
Order By: Relevance
“…To confirm the presence of MAIT cells in the metastasis and primary tumor site we analyzed a public dataset available on Gene Expression Omnibus (GSE148190) 26 . This dataset contains single-cell RNA and TCR sequencing of PBMCs and tumor-infiltrating lymphocytes from untreated patients with metastatic melanoma.…”
Section: Resultsmentioning
confidence: 99%
“…To confirm the presence of MAIT cells in the metastasis and primary tumor site we analyzed a public dataset available on Gene Expression Omnibus (GSE148190) 26 . This dataset contains single-cell RNA and TCR sequencing of PBMCs and tumor-infiltrating lymphocytes from untreated patients with metastatic melanoma.…”
Section: Resultsmentioning
confidence: 99%
“…The gene expression scRNAseq data for patients K409 and K411 (initial blood/tumor pair) and the TCR data (for tumor) can be found on GEO with accession no. GSE148190 ( Mahuron et al, 2020 ). The scRNAseq generated during this study can be found on GEO as a SuperSeries with accession no.…”
Section: Methodsmentioning
confidence: 99%
“…This study did not generate new unique reagents. The gene expression scRNA seq data for patients K409 and K411 (initial blood/tumor pair) and the TCR data (for K409 tumor) can be found on GEO with accession number GSE148190 (Mahuron et al, 2020). The scRNA-seq data generated during this study will be made available upon publication.…”
Section: Resource Availabilitymentioning
confidence: 99%